VoiText Care: ANFIS driven Persuasive Mobile Application for Medication Adherence Intervention - Uzoma R Alo (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The prevalence of medication non-adherence to long-term therapies among outpatients with chronic disease has continued to be an issue of serious concern to healthcare institutions and general public. Multifaceted intervention approach to motivate and promote positive health behavior of patients towards medication adherence is highly needed. In this paper, the design of voice and text (VoiText Care App, a persuasive mobile application that leverages patient’s assessment score of medication non-adherence level (data) with four (4) linguistic terms (variables) generated by ANFIS algorithm for delivering of personalized and persuasive adherence intervention message is proposed. The four linguistic variables (terms) of medication non-adherence level are: very low non-adherence (VLNA), low non-adherence (LNA), high non-adherence (HNA) and very high non-adherence (VHNA). With assessment score, level of non-adherence of patient is mapped with linguistic terms and it is used to determine the persuasion strategy or principle to be adopted for the composition of the persuasive messages. With combined potential of agent voice call, short message service of mobile phone technology, persuasive strategies and web portal, the developed persuasive mobile application could efficiently improve adherence to medication.